"Do you find it normal to be so fat?" Weight stigma in obese gym users. (November 2022) - Argüelles, David; Pérez-Samaniego, Víctor; López-Cañada, Elena
Weight stigma is a negative social process that involves discrimination against overweight and obese people. Gyms are important environments to promote exercise where weight stigma can be a hindrance for obese exercise practitioners. This critical-oriented study provides evidence-based answers to this question: How do obese users experience weight stigma in gyms? Six obese gym users (BMI >30) participated in semi-structured interviews and provided visual data for photo-elicitation. A thematic analysis enabled the grouping of their experiences around weight stigma into three forms of discrimination: 1) direct : negative comments about body weight and body size; 2) indirect : internalization of negative stereotypes on weight, ability or appearance; 3) structural : explicit or symbolic rejection related with weight-centric exercise, equipment and recommendations implicit in marketing and advertising. The results provide evidence and interpretations of different forms of discrimination and inequality that operate in gyms, and how they affect obese users' experiences. Based on these results, we compile a list of measures to prevent weight stigma and recommendations for exercise professionals to relate with obese users.